1998
DOI: 10.1590/s1516-14391998000100005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the interactions between polymeric chains and surfaces with different structures performed by an atomic force microscope

Abstract: Interactions between polymers and inorganic surfaces are present in a series of phenomena involving processes such as coagulation and deffloculation of ceramic powder and adsorption of organic macromolecules on the surface of implants, among others. In this work, Atomic Force Microscopy (AFM) was modified to allow the evaluation of interactions between polymeric chains and inorganic surfaces (silica) with different structures. Polymers (sulfonated polysulfone) were grafted onto AFM cantilevers. AFM force-dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…Finally the grafted spheres were washed extensively with dimethylformamide, to remove any non-bonded polymer. The success of the grafting technique was confirmed with XPS results [15] . The modified silica spheres were then attached onto AFM silicon nitride cantilevers.…”
Section: Preparation Of Afm Modified Tipsmentioning
confidence: 56%
See 2 more Smart Citations
“…Finally the grafted spheres were washed extensively with dimethylformamide, to remove any non-bonded polymer. The success of the grafting technique was confirmed with XPS results [15] . The modified silica spheres were then attached onto AFM silicon nitride cantilevers.…”
Section: Preparation Of Afm Modified Tipsmentioning
confidence: 56%
“…In Figure 2, a drawing representing the whole technique developed to measure interactions between surfaces and polymeric entities grafted on modified AFM tips (glass sphere with polymer grafts) is shown [15] . In this scenario, the polymer chains are being brought continuously in and out of contact with the surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The infrared spectra of sPEES samples do not show a clear presence of characteristic bands of sulfonic groups due to the overlapping of sulfone groups on backbone chain with signals from sulfonic acid. Nonetheless, it is possible to identify in Figure the presence of a shoulder around 1025 cm −1 associated with SO 3 stretching of sulfonic groups …”
Section: Resultsmentioning
confidence: 99%
“…Treatment of the aminosilane with boiling water, which destroys the silane network, was shown to significantly reduce silane-polymer adhesive forces (155). Similarly, the authors showed correlation between maximum adhesive forces and silanol and sulfonic acid groups as well as mechanical entanglements (156). Adhesion between glass and HDPE or LDPE (low density polyethylene) was measured using afm.…”
Section: Morphology and Polymer Orientation Morphology Of Polymer Symentioning
confidence: 88%